CP1 Darkness visible. Issue 11 (22nd October 2010) - Dobson, R; Lawden, M
Abstract : A 67-year-old lady presented with disturbed vision. Three months earlier, she had noticed lights in her vision, resembling ripples in water with light shining on it. They were constant and visible in both dark and light. Colour and night vision remained normal. She had a past medical history of a skin tumour lateral to her left eyebrow removed 12 years previously. She had no other past medical history and was not on any medication. Examination revealed normal fundi with no relative afferent pupillary defect. Acuity and colour vision were normal. Visual fields were intact to confrontation, but perimetry showed large incongruous field defects in both eyes. The remainder of the examination was normal. A diagnosis of melanoma associated retinopathy (MAR) was suspected and an electroretinogram (ERG) was obtained, which confirmed the diagnosis. A CT scan revealed two nodules in the left lung, a mass in the mediastinum and a destructive lesion in the D6 vertebral body. Histology of a pulmonary nodule revealed metastatic malignant melanoma. MAR is a rare complication of malignant melanoma, typically presenting months to years after the initial diagnosis, heralding the discovery of metastatic disease. The clinical presentation is characteristic, and ERG is the investigation of choice. To date, no specific antibody has been conclusively associated with MAR, although antibodies against various retinal components are described. The role of immunosuppressive treatment remains controversial.